THE INFLUENCE OF INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) AND COMPETENCE ON JOB SATISFACTION AND ITS IMPLICATIONS ON THE PERFORMANCE OF NON-EDUCATIONAL EMPLOYEES OF PTS - Mila Suntika; Muhammad Suparmoko; Ade Manggala Hardianto (Yayasan Education and Social Center, 2022)
The purpose of this study is to investigate performance behavior, as well as objectivity behavior and satisfaction behavior. Confirmatory research (confirmatory research), as well as (explanatory research), examines the relationship between variables and explains the causal connection (cause and effect) between variables using hypotheses that have to formulate the goal of this type of research. According to the Partial Least Squares (PLS) analysis, the competency constructs on the satisfaction of t-statistics 6.302 and 0.542 has the most significant value for t-statistics and path coefficients, which indicates that the competency construct has a positive and significant effect on PTS satisfaction